ANALISIS PENGGUNAAN METODE ALTMAN (Z-SCORE) DALAM MEMPREDIKSI TERJADINYA FINANCIAL DISTRESS PADA PT. BANK KB BUKOPIN, Tbk KOTA PARE – PARE SULAWESI SELATAN - Andi Hendra Syam; Agum Trianto Gunawan; Dicky Zulkarnain Rona Gah (Jemasi: Jurnal Ekonomi Manajemen dan Akuntansi, 2022)
This study aims to analyze the financial statements at PT. Bank KB Bukopin Tbk. Pare – Pare by using ratio analysis of liquidity, profitability and solvency the the results are entered into the Altman Z-Score Method to determine the company’s financial condition. The data source used is premier data obtained from PT. Bank KB Bukopin Tbk. Pare – Pare in 2018 – 2020. The Results of this study indicate that the financial condition of PT. Bank KB Bukopin Tbk. Pare – Pare in 2018 – 2020 which is viewed from the ratio of liquidity, profitability and solvency then entered into the Altman Z-Score method, the position is not good / bankrupt. Keywords : Altman Z-Score, Liquidity, Profitability, Solvency